CRITICAL CONTROL POINT IDENTIFICATION THROUGH TROPHOLOGICAL MEAT PRODUCTION CHAINFROM FIELD TO FORK - A. V. Borodin; I. M. Chernukha; M. A. Nikitina (Теория и практика переработки мяса, 2017)
Competitive production management is impossible without comprehensive hazard monitoring and critical parameters control at every stage of food production from raw material and auxiliary materials delivery to ready product realization, which is difficult without modern IT-support. The HACCP (Hazard Analysis and Critical Control Points) approach to product safety diﬀers from ready product testing for compliance with NaTD requirements (Normative and Technical Documentation) and emphasizes the importance of the process approach to monitoring at every stage of food production. Critical control points (CCP) identiﬁcation is a stage, where the presence of a risk of manufacturing products that are unsafe for human health is recognized and it is possible to take action to its elimination, prevention or reduction to an acceptable level. The use of soﬅware package signiﬁcantly increases the enterprise HACCP system efficiency. The article describes methodological bases for IT-approach to the CCP identiﬁcation in the trophological meat production chain from ﬁeld to fork. The algorithmic support and soﬅware for the «Decision tree», which allows detecting existing hazards, identifying risks, determining CCPs and describing them, has been developed.